Homework Help Question & Answers

Question 4 Given that f(x) = X-4 (x + 1)(x-3) Which of the following statement is...


Question 4 Given that f(x) = X-4 (x + 1)(x-3) Which of the following statement is correct? As x + -1*. f(x) — - ~; as x + -1
Question 4 Given that f(x) = X-4 (x + 1)(x-3) Which of the following statement is correct? As x + -1*. f(x) — - ~; as x + -1 f(x) → . As x + - 1+ f(x) → - 20; as x → -1-f(x) — - As x + -17 f(x) → 0; as x + -1-.f(x) → 0. As X - - 1* f(x) → 0; as X →-1-f(x) - 0.
0 0
Next > < Previous
ReportAnswer #1

Lihen_x-> - then_Pa)-> ८ (क-पाण O-4 00८- =lim -5th lin - (ह-पा-) पात्र ९-५ h-प- 0-4 (Dom गि (E-X) राण 5-X →-11 lim fod %3D x8DH --(--- स ठिण र (पर --- (पाप ६५ As xə-it, flodeo option Hence when ना स - (sth) =lim (क) Lim -5th %3D (ह-प-राणा --- स्य काPLEASE RATE IF IT WAS HELPFUL FOR YOU.

Know the answer?
Add Answer of:
Question 4 Given that f(x) = X-4 (x + 1)(x-3) Which of the following statement is...
Your Answer: Your Name: What's your source?
Not the answer you're looking for? Ask your own homework help question. Our experts will answer your question WITHIN MINUTES for Free.
Similar Homework Help Questions
Free Homework App
Download From Google Play
Scan Your Homework
to Get Instant Free Answers
Need Online Homework Help?
Ask a Question
Get Answers For Free
Most questions answered within 3 hours.